Knowledge and practice of galactogogues consumption among breastfeeding mothers in Pahang - Abdul Ghani, Radiah; Abdul Rahim, Nurshuhaida; A. Rahman, Nor Azlina (Kulliyyah of Allied Health Sciences, IIUM, 2014)
INTRODUCTION: It is well recognized that breast milk give many benefits to the infants. The best nutrition for early months of growth for normal infants is exclusive. Almost all reasons that have been documented for discontinuance of breast milk are perception of insufficient production of milk. In order to increase the amount of milk, mothers take an effort to take supplement, known as galactogogues which been claimed to increase quality and quantity of breast milk. However, the exact effect of galactogogues is still questionable. This study aims to determine the association between the effects of galactogogues on milk production and socio-demographic data, period of breastfeeding, practice of complementary breastfeeding or exclusive breastfeeding, problem during breastfeeding and frequency of consumption. Besides that, this study also aims to identify the prevalence of most preferred type of galactogogues consumption among mothers in Kuantan, Pahang. MATERIALS AND METHODS: This is a cross-sectional study and 120 respondents were selected by using purposive sampling. The questionnaire forms were distributed among mothers in Kuantan. The questionnaires consist of 61 questions which divided into four sections. Chi-square test was used to determine the association between effect of galactogogues on milk production and socio-demographic data and parameter in breastfeeding among mothers in Kuantan. RESULTS AND DISCUSSION: The result showed that there was a significant association between effect of galactogogues consumption on milk production and period of breastfeed, inadequate breast milk supply and frequency of consumption. Food was most significantly preferred as compared to herb and drug. There was a significant association between knowledge and practice of galactogogues consumption among breastfeeding mothers in Kuantan. CONCLUSION: In conclusion, knowledge of galactogogues consumption among breastfeeding mothers in Kuantan was good and the practice was prevalent among them.